Borrowing constraints, housing tenure choice and buy-to-let investors: An assignment model - Jan Rouwendal; Florian Sniekers; Ning Jia (Tinbergen Institute, 2023)
We study the effect of borrowing constraints in an assignment model of the housing market. When constraints apply symmetrically to all households, these lead to lower prices but unchanged housing consumption. When households can invest their own wealth and may differ in tastes, borrowing constraints will in general result in lower house prices and higher housing consumption for unconstrained households, while housing consumption of constrained households may fall. Binding borrowing constraints result in profitable arbitrage possibilities for buy-to-let investors. They can buy houses that are preferred by constrained households unable to finance them, and make them available as rental housing. In an equilibrium with free entry of such investors, house prices and the allocation of houses to households is the same as without borrowing constraints.
Keywords: R31; R21; G51; 330; borrowing constraints; housing tenure; arbitrage; buy-to-let investment; assignment models